Methods of calculating the efficiency of clusters and possible modalities for their development //Método de cálculo de la eficiencia de los clusters y posibles modalidades para su desarrollo - Lytvynenko, Nataliia; Khmara, Maryna; Rylach, Nataliia; Spektor, Olga; Orekhov, Serhii (Revista de la Universidad del Zulia, 2020)
AbstractThe objective of the article is to analyze the method of calculating the efficiency of high-tech clusters and alternative models of their development. Method. The methodological basis of the study is a series of general and specific cognition methods. In the research process, the following were used: the formal-logical method, the system and the structural, comparative-legal, logical-legal and other scientific research methods. Results of the investigation. Four groups of efficiency indicators of the organizational and economic regulation mechanism of the administrative activity of a business cluster are defined. The difference between traditional industrial clusters and innovation clusters is considered. Examples of successful cluster operation in some countries around the world are studied. Practical meaning. It is emphasized that the efficiency of the cluster, and therefore its development, is significantly influenced by the availability of scientific potential and activity of research institutes, as well as access to non-reimbursable funds (institutions, agencies) and the operation of technology parks. Value / originality. It is observed that due to globalization, the role of clusters in competition is increasingly important. In this context, the forms of cluster development in Ukraine were proposed, as well as examples of successful clusters in Ukraine were considered.ResumenEl objetivo del artículo es analizar el método de cálculo de la eficiencia de los clusters de alta tecnología y modelos alternativos de su desarrollo. Método. La base metodológica del estudio es una serie de métodos de cognición generales y específicos. En el proceso de investigación se utilizaron: el método formal-lógico, el sistema y los métodos de investigación científica estructural, comparativo-legal, lógico-legal y otros. Resultados de la investigacion. Se definen cuatro grupos de indicadores de eficiencia del mecanismo organizativo y económico de regulación de la actividad administrativa de un clúster empresarial. Se considera la diferencia entre los clústeres industriales tradicionales y los clústeres de innovación. Se estudian ejemplos de funcionamiento exitoso de clústeres en algunos países del mundo. Significado práctico. Se enfatiza que la eficiencia del clúster, y por ende su desarrollo, está significativamente influenciado por la disponibilidad de potencial científico y actividad de los institutos de investigación, así como el acceso a fondos no reembolsables (instituciones, agencias) y la operación de parques tecnológicos. Valor / originalidad. Se observa que debido a la globalización, el papel de los clústeres en la competencia es cada vez más importante. En este contexto, se propusieron las formas de desarrollo de clústeres en Ucrania, así como se consideraron ejemplos de clústeres exitosos en Ucrania.